Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/adfm.201202818
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of PbS Nanocrystal:C60 Fullerite Broadband Photodetectors with High Detectivity

Abstract: Hybrid PbS nanocrystal/C 60 fullerite photodetectors are fabricated using a simple one-step drop casting procedure onto pre-patterned interdigitated electrodes. The devices exhibit a broad spectral response from the near UV through to the near infrared yielding a detectivity, D * , of above 10 10 Jones from 400 nm to ≈ 1050 nm. The ability to further extend the spectral response to wavelengths ≈ 1350 nm in the near infrared via tuning of the PbS nanocrystal diameter is also demonstrated. The dynamic responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 50 publications
(59 reference statements)
0
38
0
Order By: Relevance
“…It should be noted that the photodoped devices we report here work on a fundamentally different mechanism as compared to more commonly reported planar heterojunction donor/acceptor (D/A) devices reported previously2930313233. In typical blend devices the relative donor to acceptor volume ratio is very high and the devices rely primarily on the absorption and conductivity of the donor material.…”
Section: Discussionmentioning
confidence: 72%
“…It should be noted that the photodoped devices we report here work on a fundamentally different mechanism as compared to more commonly reported planar heterojunction donor/acceptor (D/A) devices reported previously2930313233. In typical blend devices the relative donor to acceptor volume ratio is very high and the devices rely primarily on the absorption and conductivity of the donor material.…”
Section: Discussionmentioning
confidence: 72%
“…Hybrid inorganic-organic photoconductors based on type-II heterojunctions via blending PbS NCs with widely used fullerene acceptors, PCBM and C60 crystals have also been reported. 48,49 One advantage of hybrid devices is that they can operate even with oleic acid ligands as the photoexcited charge transport occurs through acceptor materials, although long ligands may supress the electron transfer process from PbS NCs to the acceptor material. In such hybrid devices both charge carriers may be collected depending upon the charge percolation pathways in the blend film and also the type of NC ligand used.…”
Section: Pbs Nanocrystal Photodetectorsmentioning
confidence: 99%
“…3 In recent years Esmaeili-Zare et al used a sonochemical technique to synthesis HgSe nanocrystals with a reported band edge of 2.23 eV. 13 The report described the use of SeCl 4 and HgCl 2 in the presence of hydrazine and capping agents, where ultrasonic waves were used to irradiate the reaction to form the required nano-crystals.…”
mentioning
confidence: 99%